Impact of blade number on performance, loss and flow characteristics of one mixed flow turbine. (15th July 2020) - Ketata, Ahmed; Driss, Zied; Abid, Mohamed Salah
Abstract: Mixed flow turbines have been widely applied in turbochargers, aircraft engines and power generation systems. It is well known that the mixed flow turbine is a seat of several losses such as secondary flow generation and incidence effects. The turbine loss is dependent on its design parameters, especially the blade number. Commonly, this last parameter is determined by old empirical correlations which are less accurate than more advanced computation methods. In the light of this, the present paper investigates the effect of the blade number using the latest advanced 3D-CFD code attempting to improve performance and further reduce loss generation. Seven designs of the mixed turbine with different numbers of blades from 3 up to 15 have been considered for investigation. Computed results have been validated against experimental data collected from a developed test rig. Two correlations have been developed relating the mass flow parameter and the output torque of the turbine to its blade number. Also, a detailed analysis on the effect of the blade number on the tip clearance flow leakage has been performed. Results showed better efficiency and a decreased blade passage loss with an increasing blade number. Highlights: Blade number effect on performance of one mixed flow turbine was investigated. Seven designs with different blade numbers have been considered for investigation. A good agreement has been recorded between numerical and experimental results. Passage and incidence losses decrease with an increasing blade number. Swallowing capacity and efficiency are improved with an increasing blade number.